2015
DOI: 10.1111/bjd.13973
|View full text |Cite
|
Sign up to set email alerts
|

Oxybutynin as a treatment for generalized hyperhidrosis: a randomized, placebo-controlled trial

Abstract: Treatment with low-dose oxybutynin is effective in reducing symptoms of hyperhidrosis in generalized or localized forms. Side-effects were frequent but minor and mainly involved dry mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Results were consistent across each study type, for each anticholinergic drug and none of the studies recorded a worsening in QOL following anticholinergic therapy. Placebo therapy was also associated with a modest improvement in QOL outcome, but the effect was not comparable to anticholinergic therapy . The mean proportion of patients who experienced improvement in QOL was 75.6% (range 57.6–100%), and these improvements were maintained at long‐term follow‐up …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Results were consistent across each study type, for each anticholinergic drug and none of the studies recorded a worsening in QOL following anticholinergic therapy. Placebo therapy was also associated with a modest improvement in QOL outcome, but the effect was not comparable to anticholinergic therapy . The mean proportion of patients who experienced improvement in QOL was 75.6% (range 57.6–100%), and these improvements were maintained at long‐term follow‐up …”
Section: Resultsmentioning
confidence: 97%
“…All of the studies documented evidence of dry mouth, and results were consistent between different drug therapies and patient cohorts. Placebo also caused symptoms of dry mouth, but these effects were not comparable to high‐dose anticholinergic therapy . Dry mouth was dose related and more common with oxybutynin therapy 10 mg/day or more .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective, randomized, placebo-controlled trial for the initial treatment of hyperhidrosis showed improvement in greater than 70% of patients with palmar and axillary hyperhidrosis and greater than 90% of patients with plantar hyperhidrosis [35]. A subsequent study showed a 60% improvement in the Hyperhidrosis Disease Severity Scale and a significant improvement in the Dermatology Life Quality Index [36]. Dosing in the literature varies greatly from 2.5 to 5 mg twice daily with dry mouth being the main dose-limiting adverse event [35, 37].…”
Section: Current Therapies For Hyperhidrosismentioning
confidence: 99%